Corruption and bureaucratic structure in a developing economy - John Bennett; Saul Estrin (Transformation, Integration and Globalization Economic Research (TIGER), 2006)
In many transition economies, insiders controlled state-owned firms, de facto. For such firms, we model the decision about privatization method, focusing on the choice between free distribution (so called 'mass privatization') and management-employee buyouts. We incorporate a political feasibility constraint that the revenue-maximising government cannot pay insiders to take firms off its hands. Although mass privatization apparently conflicts with revenue maximization, we show that nonetheless it may be the preferred method, and if so it will be complementary with the state continuing to own shares. Mass privatization is more likely to be chosen if the government is politically weak.
Keywords: D73; H11; H77; 330; Corruption; Bureaucratic Structure; Developing Economy; Korruption; Bürokratie; Privatisierung; Theorie